Pelayanan Kesehatan Bagi Masyarakat Dalam Rangka Kegiatan Pengabdian Kepada Masyarakat - Rifkind Malik; Irma Primawati; Roland Helmizar; Annisa Lidra Maribeth; Yahdian Rasyadi; Relin Yesika (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The economy and education are important aspects of the community but the other most important is health because health can affect economy and social productivity. Health can be imbalanced due to a poor lifestyle, diet, and lack of physical activity which will trigger various non-communicable diseases. The aim of this service community is to provide understanding on disease, good diet and daily physical activity. The method used is leaflets, posters, and short lectures. The result of this service is that many respondents are elderly. With this service we hope that in the future the elderly can begin to increase their physical activity, consume healthy food and routine health checks to increase the quality of life.